Antimicrobial drug use in primary healthcare clinics: a retrospective evaluation - Shamsuddin, Shafinaz; Akkawi, Muhammad Eid; Razi Zaidi, Syed Tabish; Ming, Long Chiau; Manan, Mohamed Mansor (2016)
Objectives: To examine the appropriateness of antibiotics prescribed for acute infection based on the Malaysian national antibiotic guidelines and the defined daily dose (DDD) system of the World Health Organization (WHO). This study also aimed to describe the factors influencing the drug use pattern and to investigate the procurement patterns of antibiotics in the primary healthcare setting. Methods: A retrospective cohort follow-up study of randomly selected patients from all patients who received any antibiotic between January and December 2013 was conducted at three primary healthcare clinics in Selangor State of Malaysia. For each patient, the following information was recorded: name of the antibiotic, frequency and dose, and Anatomical Therapeutic Chemical (ATC) group. The defined daily dose per 1000 inhabitants per day was calculated for each antibiotic. The national antibiotic guidelines were used to assess the appropriateness of each antibiotic prescription. Results: A total of 735 patients were included in the study. The five most used antibiotics were amoxicillin (1.36 g, 35.2%), cloxacillin (0.68 g, 26.3%), erythromycin (0.32 g, 22.3%), bacampicillin (0.13 g, 7.2%), and cephalexin (0.11 g, 6.9%). Respiratory tract infections were the most commonly treated infections, and the doctors’ preferred antibiotic for the treatment of these infections was amoxicillin. More than 18% of all amoxicillin prescriptions were deemed inappropriate according to the national antibiotic guidelines. In terms of procurement costs, USD 88 885 was spent in 2011, USD 219 402 in 2012, and USD 233 034 in 2013 at the three primary healthcare clinics, an average of USD 180 440 per year for the three clinics. Conclusions: This study reports the antibiotic usage at three primary healthcare clinics in Klang Province. The most prescribed antibiotic was amoxicillin in capsules (250 mg), which was mainly prescribed for respiratory infections. Although the national antibiotic guidelines state that amoxicillin is a preferred drug for acute bacterial rhinosinusitis, this drug is also being prescribed for other disease conditions, such as acute pharyngitis and acute tonsillitis. This result shows that current practice is not following the current antibiotic guidelines, which state that phenoxypenicillin should be the preferred drug.